Possibilities and scope of renal angiography - Viola Peluffo, Julio C (Cirugía del Uruguay, 1971)
We hold the concept that renal angiography constitutes an exception as a diagnostic method in general surgery. It is used relatively frequently in diagnosis renal processes, constituting a non-current technique as a procedure that has its specific indications in certain processes.